INTEREST, WILL AND NEUROLAW - Primak; Finogentova; Kitsai , Juliana; Fedorov; Zyryanova (Revista Inclusiones, 2020)
Interest and will are legal phenomena and elements of the motivational complex of human behavior. The discoveries of neurosciences and neurotechnologies expand knowledge about human behavior and the psychological and biological characteristics of interest and will. They form new directions, including neurolaw, which is not only widely used in practical terms but also changes traditional legal views, for example, on free will – a fundamental category of jurisprudence. Goal: To analyze existing and identify new approaches to the study of interest and will in the context of neurolaw, which will allow identifying new behaviors.